Implikasi Pernikahan Sebagai Sanksi dari Pacaran dalam Perspektif Maqasid Syari’ah dan Hak Asasi Manusia (HAM) - Iqbal, M (-, 2024)
Marriage is prescribed to obtain a life that is sakinah, mawaddah and warahmah. To obtain the goals, the marriage must start in the way recommended by sharia in the form of muqaddimah such as ta'aruf and khitbah. However, there is a different way in society where marriage begins with the principle of courtship. For reasons of maintaining the good name and dignity of the family and also other reasons, this marriage was carried out as a result of the act of courtship. Therefore, this research was carried out to find out the legal implications of marriage based on dating, with a research approach in the form of qualitative research, and also data sourced from primary data obtained from events in society, and also secondary data obtained from various literature. Fiqh books and also journals related to the topics discussed. The results of this research show that all the reasons taken in the act of marrying the dating couple are in accordance with Maqashid sharia and occupy a position of dharuriyat (primary) needs, so that this marriage contains great benefits for women and all parties related to this case. Meanwhile, based on human rights, this marriage will have implications for the destruction of women who are abandoned by men if this marriage does not take place. So, marriage which results from the act of dating can become a law that has a deterrent effect and a law that brings preventive action for teenagers who like to date. So it becomes a legal solution to the rampant promiscuity that occurs through dating.